Comprehension assessment of information about medicines use among hospitalized orthopedic patients - Ćetković, Zora; Krajnović, Dušanka (Archives of Pharmacy, 2022)
Patients with orthopedic injury are at high risk of venous thromboembolism. Although anticoagulant therapy is the mainstay, traditional oral anticoagulants have unpredictable pharmacokinetics, require regular monitoring and may cause side effects. The aim of this study was to assess knowledge, comprehension of information about medicines use and access to medicines-related information among adult hospitalized orthopedic patients. The research was conducted as a cross-sectional study at the Clinic for Orthopedic Surgery and Traumatology, University Clinical Center of Serbia, from September to November 2021. Specific and socio-demographic questionnaires were used to assess patients’ comprehension of information about medicines use. The study included 110 patients (response rate 94%); 56.4% of the included patients were men, 80% were older than 30 years and 67.3% completed higher education. The results showed that most patients (53.6%) use the Patient Information Leaflet (PIL) to obtain information about medicines use, or the medicine information box to aquire information about medicines storage, while only 32.7% of patients rely on pharmacists to provide advice. Most orthopedic patients (˃55%) understood information about medicines use and storage, except for the information related to the shelf life of the medicine (82.7% incorrect answers). This study indicates that hospitalized orthopedic patients are more likely to find medicines information by themselves rather than asking pharmacists, which can lead to a lack of comprehension of cruical information about medicines and affect treatment outcomes. Therefore, communication between healthcare professionals and patients should be improved during hospitalization and discharge.